Phenology analysis growing and degree days of flower bud growth in three Dianthus caryophyllus L. varieties under greenhouse conditions - Leguízamo-Medina, María Fernanda; Pinzón-Sandoval, Elberth Hernando; Balaguera-López, Helber Enrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The production of carnations (Dianthus caryophyllus L.) in Colombia is a very important economic activity. Therefore, predicting harvests is vital for the market. The phenological behavior and growth of carnations during the flowering season in the cultivars Idilio, Ilusion, and Moon light were determined in greenhouse using a functional growth analysis. This research was based on the phenological stages and accumulation of growing degree day (GDD), relating the temperature in terms of thermal time with the development of flower buds from the rice point phenological stage to cut-off point 5. There were eight stages of carnation flower bud development; rice, pea, chickpea, barrel, star, bullet, cut point 3, and cut point 5. The fresh and dry mass of the flower buds in the three varieties presented a simple sigmoid growth pattern that was adjusted to a logistic model. There were three growth phases: phase 1, which was from the pea stage to barrel stage with accumulation of 380.7 GDD in the Idilio cultivar, 381.5 GDD for ‘Ilusion’, and 361.6 GDD for ‘Moon light’. Phase 2 ended with the bullet stage, where the accumulation was 294.4 GDD, 397.7 GDD, and 293.5 GDD for ‘Idilio’, ‘Ilusion’ and ‘Moon light’, respectively. In phase 3, ‘Idilio’ accumulated 108.9 GDD, ‘Ilusion’ had 110.8 GDD, and ‘Moon light’ showed 99.9 GDD. Moon light was the earliest cultivar, and Ilusion was the latest variety.